Tantangan Legalitas UMKM di Indonesia: Upaya Pemerintah dalam Penerbitan NIB Untuk Mendukung Pertumbuhan Ekonomi di Kabupaten Bantul - Syafira Elena; Indra Lesmana; Helen Dian Fridayani; Achmad Nurmandi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political UMA), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in driving regional economic growth; however, the level of business legality, as indicated by Business Identification Number (NIB) ownership, remains uneven across regions. This study aims to analyze the spatial distribution of MSMEs and disparities in NIB ownership in Bantul Regency, and to examine the role of the local government in promoting business formalization. A mixed-methods approach is employed, combining qualitative descriptive analysis with spatial analysis using Geographic Information Systems (GIS). Secondary data were collected from local government agencies, the Central Statistics Agency (BPS), and relevant scientific literature, covering approximately 96,000 MSMEs at the subdistrict level. Data analysis was conducted using the interactive model of Miles and Huberman, integrated with spatial mapping techniques. The findings reveal that while MSMEs are widely distributed, NIB ownership remains uneven, particularly in peripheral areas. This disparity is influenced by limited digital literacy, unequal access to digital infrastructure, and variations in government outreach and institutional capacity. The study highlights that spatial factors and governance effectiveness significantly shape business legality. It contributes to the literature by incorporating spatial perspectives into MSME legality studies and emphasizes the importance of place-based policy interventions to support inclusive and sustainable business formalization.